(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A pan-tropical plant known as benzolive, drumstick tree, kelor, marango, mulangay, nébéday, saijan, and sajna is Moringa oleifera or horseradish tree. Many studies on its nutritional and medicinal properties have appeared over the past two decades in popular medical journal publications. It has also been defined in detail, although it is not mentioned in this text, its usefulness as a non-food commodity (e.g. wood, charcoal, water clarification, lubricating oil). There is a very high level of healthy feed providers who now promote, like other studies on a natural product’s nutritional or medicinal value. As a panacea, oleifera although much of this new enthusiasm seems justified, strict scientific evidence must be separated from anecdotes. It is essential. The best available evidence should be offered in regions where there is a shorter hope so that false expectations are not raised and the use of limited research resources is promoted to the most fruitful.